Understanding school bullying its nature & prevention strategies - Smith, Peter K. 1943- (SAGE, 2014)
This new book, by a leading international expert on the topic, brings together the cumulative knowledge acquired and the latest research findings in the area, with a global perspective especially covering research in Europe, North America, Australasia, and Asia